Contested ground : how to understand the limits of presidential power - Farber, Daniel A., 1950- (University of California Press, 2021)
"Presidential power is hotly disputed these days - as it has been many times in recent decades. Yet the same rules must apply to all presidents, those whose abuses of power we fear as well as those whose exercises of power we applaud. This book is about what constitutional law tells us about presidential power and its limits. It is very difficult to strike the right balance between limiting abuse of power and authorizing its exercise when needed. This book advocates a balanced, pragmatic approach to these issues, rooted in history and Supreme Court rulings"--